2013
DOI: 10.2174/1874306401307010071
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Metabolic Syndrome in Spanish Population

Abstract: Obstructive sleep apnea (OSA) is a clinical picture characterized by repeated episodes of obstruction of the upper airway. OSA is associated with cardiovascular risk factors, some of which are components of metabolic syndrome (MS).Objectives:First, determine the prevalence of MS in patients with OSA visited in sleep clinic. Second, evaluate whether there is an independent association between MS components and the severity of OSA.Methods:Patients with clinical suspicion of OSA were evaluated by polysomnography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…After review by title and abstract, 529 were eliminated for not being relevant. The full texts of the remaining 20 studies were further assessed for eligibility and 10 articles were excluded, for the reasons shown in Figure 1; thus, 10 studies with a total of 2053 patients were included in the meta-analysis [2,24,[34][35][36][37][38][39][40][41]. Two were cross-sectional studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…After review by title and abstract, 529 were eliminated for not being relevant. The full texts of the remaining 20 studies were further assessed for eligibility and 10 articles were excluded, for the reasons shown in Figure 1; thus, 10 studies with a total of 2053 patients were included in the meta-analysis [2,24,[34][35][36][37][38][39][40][41]. Two were cross-sectional studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…In 2013, Barreiro et al, found a prevalence of 82.2% of OSA and a significant association with the components of MetS in a sample of 141 patients with MetS. 21 All the indicators of the syndrome have significant association on the cardiovascular and cerebrovascular systems, so it is essential to treat every individual component to decrease the morbidity and mortality. 2 According to some similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…28 Thus, our study adds to the growing body of literature that supports expansion of testing in these populations which may be at higher risk than previously estimated. 29,30 …”
Section: Discussionmentioning
confidence: 99%